Rethinking the French new right : alternatives to modernity - Bar-On, Tamir. (Routledge studies in extremism and democracy ;, 2013)
"This book focuses on the philosophy, politics and impact of the 'New Right' which originated in France and has since influenced activism, ideology and policy in a number of European countries"--